Online social networks and using them to improve social skills in young people with disabilities - Suriá Martínez, Raquel (Escritos de Psicología - Psychological Writings, 2012)
In recent years, online social networks have introduced profound changes in our environment and new ways of relating to others. The use of social networks is increasingly common, especially among young people, and could further empower young people with limited mobility as a result of a disability. This paper examines the opinions of young people with motor disabilities about the friendships they maintain over online networks and their perceptions regarding how these networks improve their social skills. This is discussed in reference to gender, age and occupation. 68 young people with physical disabilities answered an online questionnaire created for this purpose. The results were analyzed using quantitative methodology. Although we found significant differences based on gender, age and occupation, most of the young people perceived themselves as being highly motivated to use these spaces for personal relationships. They also value the networks in improving their social skills. These results suggest that online social networks are important to young people with physical disabilities in their social relationships, and may also help to design programs aimed at promoting social integration.